Mit uniwersalnej biblioteki i idea definitywnej książki: konteksty i kontrowersje - Melosik, Zbyszko (Studia Edukacyjne, 2023)
The article is aimed at describing two examples of man’s dream about totality. In the introduction, the author considers the concept of a universal library and definitive book. The first part includes an analysis of various existential conceptions of total library, and first of all, Borgesian, presented in his famous text “Library of Babel” as well as his concept of Aleph as a universal point with its access to the whole reality. Also, the catastrophic idea of a universal library created by Kurt Lasswitz is presented. The second part of the article is devoted to the concept of a definitive book. Here the famous text written by Borges “The Book of Sand” is considered. Besides the author presents the idea of universality included in the Enlightenment encyclopedias as well as the scientific Biblia project developed by Novalis. In the last part of the article, a comparison is made between the physical library and the virtual library.